Imaging Findings in Osteogenesis Imperfecta - Dorigatti Soldatelli, Matheus; Döwich, Vanessa; Maybe Bedinot da Conceição, Thaylla; Maria Félix, Têmis (Clinical and Biomedical Research, 2017)
A 14 months -old male patient is brought to the outpatient clinic with a history of multiple bone fractures, he was born with fractures in left femur and humerus and presented 3 more fractures until the first consultation. There was no family history of genetic disorders and consanguinity. At physical examination, short stature for his age, discolored and translucent teeth, triangular face shape and bluish color of eye sclera were noticed. Initial radiographic studies of bones showed diffuse signs of osteoporosis, deformed limb bones and multiple long bone fractures with different ages. The radiograph of the skull showed small intra-sutural bones in between the cranial sutures, known as Wormian bones (figure 1). Diagnosis of osteogenesis imperfecta (OI) was confirmed and treatment with cyclic sodium pamidronate was started. At 3 years old a total of ten fractures were reported on tibias, femurs and proximal left humerus. The following radiographic studies showed the “zebra stripe sign” - sclerotic growth recovery lines in the metaphysis of long bones (figures 2 and 3). Palavras-chave: Osteogenesis imperfecta; pediatrics; radiology